Guideline and indicators for Target 6.6 of the SDGs: “Change in the extent of waterrelated ecosystems over time” - Dickens, Chris; Rebelo, Lisa-Maria; Luxon, Nhamo (CGIAR Research Program on Water, Land and Ecosystems, 2017)
This guideline provides supporting information to assist with implementation of monitoring procedures for Target 6.6 indicator, which focuses on protecting and maintaining water-related ecosystems.